(untitled) - Hopcroft, John E. (Boston, 2007)
This classic book on formal languages, automata theory, and computational complexity has been updated to present theoretical concepts in a concise and straightforward manner with the increase of hands-on, practical applications. This new edition comes with Gradiance, an online assessment tool developed for computer science.
Tin học lý thuyết,Lý thuyết tính toán
Keywords: Machine theory,Formal languages,Computational complexity,Lý thuyết máy,Ngôn ngữ hình thức,Độ phức tạp của máy điện toán